Two sides of child maltreatment: from psychopathic traits to altruistic attitudes inhibition - Carvalho, Alexandra (2020)
Child maltreatment is a known risk factor for criminal behavior, however, only a few studies have addressed the relationship between child maltreatment and the development of psychopathic traits. Meanwhile, the effect of adverse childhood experiences on prosocial behavior is practically unknown. The current research aims to explore the relationship between child maltreatment, psychopathic traits and altruistic attitudes among young adults. Six hundred and seventy-three young adults from the community filled out the Adverse Childhood Experience Questionnaire, the Youth Psychopathic Traits Inventory - Short Version and the Altruistic Attitudes Scale. Results suggest that child maltreatment is related to both psychopathic traits and inhibition of altruistic altitudes. Each adverse childhood experience appears to be associated with the development of specific forms of psychopathic traits and/or altruistic attitudes. Early identification of maltreatment is essential for prevention of antisocial behavior and for the promotion of altruistic attitudes. Research, political and social recommendations are suggested.